Analysis of the Corn Supply Chain to Increase Farmers’ Profits in Napis Village - Nur Faizah (Fakultas Teknik Universitas Negeri Surabaya, 2026)
Bojonegoro Regency, particularly Napis Village in Tambakrejo District, is a major corn-producing center in East Java that faces supply chain challenges such as limited access to capital, fluctuations in input costs, and low bargaining power among farmers due to their dependence on informal middlemen. This study aims to identify the factors affecting farmers’ profits, develop and validate a Dynamic Systems model based on actual data from 2021–2025, and formulate strategies for strengthening a sustainable supply chain. A combined PLS-SEM and Dynamic Systems (STELLA) approach was applied using data from 60 respondents. The PLS-SEM analysis confirmed that access to capital is the most dominant factor influencing profits (path coefficient = 0.504; T-statistic = 4.947; P-value = 0.000). Simulations of three scenarios (2026–2030) showed that the scenario involving labor substitution through the adoption of collective corn planting technology managed by Gapoktan (Scenario 3) was the best option because it reduced operating costs by Rp4.36 billion without increasing farmers’ debt burden. Gapoktan-based supply chain restructuring breaks farmers’ financial dependence on middlemen and restores farmers’ bargaining power in determining corn selling prices.